Fall prevention interventions for Hispanic/Latino older adults: a scoping review protocol - Lopez, Janet; Dino, Michael Joseph; Banarjee, Chitra; Thiamwong, Ladda (Frontiers in Public Health, 2025)
BackgroundDespite the importance of fall prevention among older adults, limited research exists on interventions tailored to rapidly growing Hispanic/Latino populations in the United States. This protocol paper outlines the rationale and methods for conducting a scoping review to address this knowledge gap.Methods and analysisWe will follow Arksey and O’Malley’s framework and Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for scoping reviews (PRISMA-ScR). This scoping review will be guided by the following research questions: What characterizes fall prevention interventions for Hispanic/Latino older adults? An iterative and systematic search of peer-reviewed publications from four databases (PubMed, PsycINFO, Web of Science, and CINAHL) will be extracted and uploaded to Covidence for screening.Trial registrationThis scoping review protocol has been registered with Open Science Framework and can be accessed at https://osf.io/zx3m8.